Integrating plasmasphere, ionosphere and thermosphere observations and models into a standardised open access research environment: The PITHIA-NRF international project - Anna Belehaki; Ingemar Häggström; Tamas Kiss; Ivan Galkin; Anders Tjulin; Mária Miháliková; Carl-Fredrik Enell; Gabriel Pierantoni; Yin Chen; Gergely Sipos; Sean Bruinsma; Viviane Pierrard; et al. (Advances in Space Research, 2025)

Validation of global ionospheric models using long-term observations of pulsar Faraday rotation with the LOFAR radio telescope - Nataliya K. Porayko; Maaijke Mevius; Manuel Hernández-Pajares; Caterina Tiburzi; German Olivares Pulido; Qi Liu; Joris P. W. Verbiest; Jörn Künsemöller; Moochickal Ambalappat Krishnakumar; Ann-Sofie Bak Nielsen; Marcus Brüggen; Victoria Graffigna; et al. (Journal of Geodesy, 2023)
Broad band pulsar radiation can be effectively used to monitor the properties of the magneto-ionic media through which it propagates. Faraday rotation calculated from polarised pulsar observations provides an integrated product of electron densities and the line-of-sight component of the magnetic field in the intervening plasma. In particular, a time-variable effect mainly associated with the rapidly changing column density of the Earth’s ionosphere and plasmasphere heavily dominates the observed Faraday rotation of pulsar radiation. In this work, we aim to carry out a performance test of three GNSS-based models of the ionosphere using observations of PSR J0332+5434 taken with the LOw Frequency ARray (LOFAR). As it was shown in Porayko et al. (Month Not Roy Astron Soc 483(3):4100–4113, 2019. https://doi.org/10.1093/mnras/sty3324 . arXiv:1812.01463 ), the conventional single layer model (SLM), which assumes that the ionosphere is a thin slab at a fixed effective height, is not capable of fully accounting for the ionospheric Faraday rotation in pulsar data. The simplified physics of the SLM is upgraded within IRI-Plas (International Reference Ionosphere and Plasmasphere) extended SLM and the dual-layer voxel TOmographic Model of the Ionosphere (TOMION), both of which partially account for the thickness and vertical dynamics of the terrestrial plasma. Although the last two improve the reconstruction of the ionospheric Faraday rotation, none of the considered models completely purge the observed residual variations. With this study, we show that the long term LOFAR observations of Faraday rotation of pulsars provide an excellent tool to test and improve models of the magneto-ionic content of the Earth’s atmosphere.

Ionospheric tomographic common clock model of undifferenced uncombined GNSS measurements - Germán Olivares-Pulido; Manuel Hernández-Pajares; Haixia Lyu; Shengfeng Gu; Alberto García-Rigo; Victoria Graffigna; Dariusz Tomaszewski; Paweł Wielgosz; Jacek Rapiński; Anna Krypiak-Gregorczyk; Rafał Kaźmierczak; Raul Orús-Pérez (Journal of Geodesy, 2021)
In this manuscript, we introduce the Ionospheric Tomographic Common Clock (ITCC) model of undifferenced uncombined GNSS measurements. It is intended for improving the Wide Area precise positioning in a consistent and simple way in the multi-GNSS context, and without the need of external precise real-time products. This is the case, in particular, of the satellite clocks, which are estimated at the Wide Area GNSS network Central Processing Facility (CPF) referred to the reference receiver one; and the precise realtime ionospheric corrections, simultaneously computed under a voxel-based tomographic model with satellite clocks and other geodetic unknowns, from the uncombined and undifferenced pseudoranges and carrier phase measurements at the CPF from the Wide Area GNSS network area. The model, without fixing the carrier phase ambiguities for the time being (just constraining them by the simultaneous solution of both ionospheric and geometric components of the uncombined GNSS model), has been successfully applied and assessed against previous precise positioning techniques. This has been done by emulating real-time conditions for Wide Area GPS users during 2018 in Poland.

Retrieving geophysical signals from GPS in the La Plata River region - Victoria Graffigna; Claudio Brunini; Mauricio Gende; Manuel Hernández-Pajares; Romina Galván; Fernando Oreiro (GPS Solutions, 2019)